Architectural Style Application of Mayor Office’s and Ria Cinema’s Building in Pematangsiantar - Morida Siagian; Rumini Manurung (Talenta Publisher, 2018)
The development of architecture in Indonesia cannot be separated from foreign countries; we can see from the many forms of buildings in Indonesia that adopted the overseas architectural styles, one of them is Dutch Colonial Architecture Style. Pematangsiantar is one of the city that got influence from Dutch Colonial in architecture. The Building of The Mayor Office and the Ria Cinema is including the building of the colony’s historical relics around The H. Adam Malik Park Pematangsiantar that applied The Dutch Colonial Architectural Style. This research reviewed the application of Dutch Colonial Architectural Style in Indonesia in the building of The Mayor Office and Ria Cinema in Pematangsiantar. This research used the descriptive qualitative method that is, the data generated through direct observation of the object research and conduct literature study by studied the results of research and books related to Dutch Colonial Architecture Style in Indonesia. The results showed that the building of The Mayor Office in 1920, Pematangsiantar dominantly applied The Dutch Colonial Architectural Style in Indonesia in Period of 1800s-1902, Ria Cinema Pematangsiantar dominantly applied The Dutch Colonial Architectural Style in Indonesia in Period of 1920s-1940s.